'Communities with Oomph'? Exploring the Potential for Stronger Social Ties to Revitalise Disadvantaged Neighbourhoods. (April 2013) - Crisp, Richard
Successive governments in the UK have claimed that strengthening social ties can revitalise the fortunes of disadvantaged areas. This claim has been critiqued extensively by urban scholars for failing to understand the nature of lived urban social relations. However, less attention has been given to mapping out the terrain of this criticism, despite the different positions adopted by scholars and, by extension, the divergent implications for public policy. With this paper I address this gap by identifying and reflecting on two of the most prominent frameworks of critique. I draw on empirical research of social ties in two deprived neighbourhoods in England to assess the validity of these frameworks and their applicability in different spatial contexts. I conclude that both provide useful insights into the dynamics of change and the limits of existing policy but, also, that the specificity of each account is perhaps overlooked.